PROUCTION AND CHARACTERIZATION OF Al-xNi IN SITU COMPOSITES USING HOT PRESSING - YAMANOGLU, RIDVAN (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
In this study, a new metal matrix composite of aluminium was designed with the addition of nickel alloy particles. To produce in situ intermetallic formation, aluminium-nickel powder mixtures with different ratios ranging from 5 to 40 wt% Ni were consolidated at 550 oC for 15 minutes under 40 MPa pressure. The interlayer phase formed during sintering was determined using X-ray diffraction and energy dispersive X-ray spectroscopy. The effect of nickel and Al-Ni intermetallics on the mechanical properties of the material was studied. The results demonstrated that the addition of nickel enhanced the hardness and wear behaviour of aluminium by forming a strong bonding interface between the aluminium and nickel particles.